Ownership Structure Effect on the Stock Returns for Companies Listed in Palestine Exchange - Asmar , Muath; Al-Thaher, Mofed; Shraim, Omar (Jordan Journal of Business Administration, 2023)
This study aimed at identifying the impact of the ownership structure on the stock returns of the public companies listed in the Palestine Stock Exchange. In order to achieve this goal, panel data for the period from 2009 to 2019 was collected from the financial reports of the 46 public companies listed in the Palestine Stock Exchange. In this study, the fixed-effect method was used in the analysis of the study’s panel data. The results of the study showed a positive effect of the ownership of major shareholders on equity returns and a negative effect of the ownership of board members on equity returns. Furthermore, the study found no significant effect of institutional ownership, foreign ownership or executive-management ownership on equity returns. In light of the study’s findings, the study made several recommendations to investors, legislators and board members regarding the ownership structure and stock returns.